2012
DOI: 10.1021/ja211011k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in Vitro Encapsulation of Protein Cargo by an Engineered Protein Container

Abstract: An engineered variant of lumazine synthase, a nonviral capsid protein with a negatively charged luminal surface, is shown to encapsulate up to 100 positively supercharged green fluorescent protein (GFP) molecules in vitro. Packaging can be achieved starting either from intact, empty capsids or from capsid fragments by incubation with cargo in aqueous buffer. The yield of encapsulated GFP correlates directly with the host/guest mixing ratio, providing excellent control over packing density. Facile in vitro load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 27 publications
4
131
0
1
Order By: Relevance
“…In addition, Hilvert and coworkers reported that engineered nonviral protein capsids such as lumazine synthase from Aquifex aeolicus are also applicable as nano-carriers for proteins and DNA. [14][15][16] Currently, however, functional modification of natural protein capsules, such as plant viral capsids and virus-like lumazine synthase capsids, requires complicated technologies such as gene recombination and protein expression. Therefore, the reconstruction of virus-like nanocapsules from synthetic molecules would enhance their potential for molecular designs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hilvert and coworkers reported that engineered nonviral protein capsids such as lumazine synthase from Aquifex aeolicus are also applicable as nano-carriers for proteins and DNA. [14][15][16] Currently, however, functional modification of natural protein capsules, such as plant viral capsids and virus-like lumazine synthase capsids, requires complicated technologies such as gene recombination and protein expression. Therefore, the reconstruction of virus-like nanocapsules from synthetic molecules would enhance their potential for molecular designs.…”
Section: Introductionmentioning
confidence: 99%
“…This selection formed the basis of a screen for mutants of AaLS that could better protect its host, presumably through improving encapsulation owing to increased negative charges on its interior surface. These improved capsids, called AaLS-13, can be isolated and loaded in vitro with monomers of GFP that have been mutated to bear 29 additional positively charged residues (Wörsdörfer et al 2011a), or even with similarly engineered human ferritin (Beck et al 2014). Ferritin is itself a small microcompartment, 12 nm in diameter, that binds and stores iron.…”
Section: Building Spatial Synthetic Biologymentioning
confidence: 99%
“…For instance, Hilvert's group engineered an artificial protein container, a variant of lumazine synthase that forms icosahedral capsids capable of spontaneously encapsulating various proteins through electrostatic interactions [37,38].…”
Section: Drug Encapsulation Through Noncovalent Interactionsmentioning
confidence: 99%